Enhancing Virus Resistance in Crops through eIF4E Knockdown: Prospects and Challenges - Abbasi, Hammad Ahmed; Anjum, Muhammad Naveed; Muhammad Atif (Integrative Plant Biotechnology, 2025)
Emerging viral diseases pose a significant threat to global food security, impacting crop yield and quality. eIF4E, a crucial translation initiation factor, is often exploited by certain viruses for replication within the host. The knockdown mutation of eIF4E has demonstrated effectiveness in conferring resistance to a range of viruses, including potyviruses and mycoviruses, with long-lasting effects that limit viral adaptation. Several gene editing approaches such as RNA silencing, TILLING, and CRISPR/Cas9 have been utilized to achieve the eIF4E knockdown. While this strategy holds substantial promise, its implementation must consider potential implications for plant growth and productivity. This review explores the potential of eIF4E knockdown for enhancing virus resistance in crops, along with recent advancements, existing challenges, and future directions for its application in sustainable agriculture.